Principles of career growth of employees of the Security Service of Ukraine - Yuzyshen, M. S.; Юзишен, М. С. (Legal, Economic Science and Praxis. - 2023. - № 8. - P. 51-56, 2023)
У статті досліджено принципи кар’єрного зростання працівників СБУ. Вказується, що серед засобів забезпечення ефективності діяльності співробітників Служби безпеки України особливе місце займає кар'єрне зростання, що виявляється в переведенні працівника, який показує високі результати в роботі, демонструє організаторські здібності, на вищу посаду. Можливість кар'єрного росту та правильне застосування переведення на вищу посаду, не в останню чергу, залежить від розуміння принципів кар’єрного росту співробітників Служби безпеки України. Визначено принципи кар’єрного зростання працівників Служби безпеки України.

The article examines the principles of career growth of employees of the Security Service of Ukraine. It is indicated that among the means of ensuring the effectiveness of the activities of the employees of the Security Service of Ukraine, a special place is occupied by career growth, which is manifested in the transfer of an employee who shows high results in work, demonstrates organizational abilities, to a higher position. The possibility of career growth and the correct application of transfer to a higher position depends not least on understanding the principles of career growth of employees of the Security Service of Ukraine. The acquisitions of scientists regarding the essence and varieties of the principles of career growth of employees are studied. The current state of national legislation regarding career regulation in the Security Service of Ukraine is considered. The principles of career growth of employees of the Security Service of Ukraine have been defined. Thus, the principles of career growth of employees of the Security Service of Ukraine are the following: the principle of optimality of personnel selection for the Security Service of Ukraine; the principle of fair career growth; the principle of unlimited career growth within the Security Service of Ukraine; the principle of gender parity in career growth in the Security Service of Ukraine; the principle of continuity of career growth in the Security Service of Ukraine; the principle of harmonious combination of the goals of the Security Service of Ukraine and the goals of its specific employee; the principle of taking into account the peculiarities of the career potential of a specific employee of the Security Service of Ukraine, his needs, interests and opportunities; the principle of proportionality and optimality of career growth. The essence of the mentioned principles of career growth of employees of the Security Service of Ukraine is revealed.

В статье исследованы принципы карьерного роста работников СБУ. Указывается, что среди средств обеспечения эффективности деятельности сотрудников Службы безопасности Украины особое место занимает карьерный рост, что проявляется в переводе работника, показывающего высокие результаты в работе, организаторские возможности, на высшую должность. Возможность карьерного роста и правильное применение перевода на высшую должность, не в последнюю очередь зависит от понимания принципов карьерного роста сотрудников Службы безопасности Украины. Определены принципы карьерного роста работников Службы безопасности Украины.
Keywords: службовець; Служба безпеки України; принципи; кар’єрне зростання; посада; правове регулювання; employee; Security Service of Ukraine; principles; career growth; position; legal regulation; служащий; Служба безопасности Украины; принципы; карьерный рост; должность; правовое регулирование